Antiviral activity of geldanamycin and its derivatives against influenza virus - Thongchai Taechowisan, Tipparat Samsawat, Winyou Puckdee, Waya S. Phutdhawong (Journal of Applied Pharmaceutical Science, 2020)
Two new geldanamycin derivatives such as 17-(tryptamine)-17-demethoxygeldanamycin (2) and 17-(5′-methoxytryptamine)-17-demethoxygeldanamycin (3) were synthesized by nucleophilic substitution of the C17 methoxyl of geldanamycin (1). Their antiviral activity was evaluated based on influenza virus propagation in embryonated chicken eggs and viral absorption by hemagglutination (HA) inhibition test. The findings indicated that these compounds inhibited viral propagation at a concentration of 12.5 μg/ml. For the viral absorption, only compounds 2 and 3 inhibited HA at a concentration of 50 μg/ml. The solubility of compounds 2 and 3 in water was 290 and 306 μM, higher than that of compound 1 about 1.91 and 2.01 times, respectively. The compounds 2 and 3 showed a moderate cytotoxic activity on LLC-MK2 and Vero cells with IC50 values of >200.00 μg/ml. These results demonstrated the invention of tryptamine-geldanamycin hybrids to prevent influenza virus infection in viral absorption and viral propagation steps.
Keywords: Antiviral activity, endophytic actinomycetes, geldanamycin, influenza virus, tryptamine-geldanamycin hybrids.